2005
DOI: 10.1093/jn/135.12.2857
|View full text |Cite
|
Sign up to set email alerts
|

Isomalto-Oligosaccharides Polarize Th1-Like Responses in Intestinal and Systemic Immunity in Mice

Abstract: Isomalto-oligosaccharides (IMO) belong to a group of prebiotics that significantly increase the number of protective gut microflora. In the present study, we investigated the effects of IMO on intestinal and systemic immunity in mice. When mice were fed a diet supplemented with 20% IMO for 4 wk, the number of lactobacilli and the levels of IgA in feces were greater than those of mice fed the control diet (P < 0.05). Interferon-gamma (IFN-gamma) production by intestinal intraepithelial lymphocytes (i-IEL) in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 40 publications
0
44
0
3
Order By: Relevance
“…The results suggest that the suppression of eosinophil infiltration in the small intestine was independent of the prebiotic action of GOS, as shown by Sonoyama et al [12] for eosinophil infiltration in the bronchium. Many reports have shown that dietary oligosaccharide modulates the immune function of the small intestine through a change in the large intestinal microbiota [7,11]. However, it is plausible that GOS directly affects the immune function of the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that the suppression of eosinophil infiltration in the small intestine was independent of the prebiotic action of GOS, as shown by Sonoyama et al [12] for eosinophil infiltration in the bronchium. Many reports have shown that dietary oligosaccharide modulates the immune function of the small intestine through a change in the large intestinal microbiota [7,11]. However, it is plausible that GOS directly affects the immune function of the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…While MO may exhibit immunoregulatory activity [63], the intake of IMO decreases serum cholesterol concentrations and improve bowel movement, stool output, and microbial fermentation in the colon [64]. IMOs also upregulate the Th1 response that play a triggering role in allergic diseases, such as rhinitis, asthma, and eczema [65].…”
Section: Alpha-glucan Acting Enzymesmentioning
confidence: 99%
“…Los valores resultantes del cociente acetato/propionato en cada una de las muestras de rata analizadas (Tabla 7) muestran que en el contenido del ciego y del colon de las ratas alimentadas con FOS y sorbitol el cociente acetato/propionato es menor mg IgAs/g peso seco), respecto al grupo control 1,179±0,349 mg IgAs/g peso seco. Aumentos significativos de IgAs en heces han sido observados previamente por otros autores en ratones cuando son alimentados con prebióticos como los FOS ó isomalto-oligosacáridos (Hosono et al, 2003;Mizubuchi et al, 2005). La cuantificación de la IgAs en las muestras de colon y ciego de los animales no fue posible por la falta de reproducibilidad de los resultados, debido probablemente a la existencia de proteasas en las muestras, resistentes a los inhibidores utilizados en el ensayo.…”
Section: Resultados Y Discusiónunclassified
“…Se encuentra en todas las mucosas y secreciones del organismo pero principalmente en la mucosa intestinal, donde su papel fundamental es la neutralización de virus y antígenos proteicos alimentarios, impidiendo su entrada al torrente sanguíneo y participando en la presentación antigénica. La cuantificación de los niveles de IgAs en muestras intestinales se realiza generalmente mediante la técnica de inmunoensayo enzimático (ELISA) tipo sándwich y ha sido previamente utilizada por otros autores en el estudio del efecto de prebióticos como isomaltooligosacáridos o inulina en el sistema inmune (Mizubuchi et al, 2005;Roller et al, 2004).…”
Section: Investigación De Prebióticos In Vivounclassified
See 1 more Smart Citation